A Critical Reassessment of Huntington’s “Clash of Civilizations” Thesis - Zahra Seif-Amirhosseini (International Institute of Islamic Thought, 2013)
My critique of Samuel Huntington’s “clash of civilizations” thesis is divided into three sections. The first section provides a critical reassessment of his definition of civilization, modernization and westernization from an Islamic perspective, or, more broadly, a religio-traditional understanding of civilization and its various historical manifestations. I also present an academic critique from the perspective of political science and sociology. Consequently, these two perspectives are sometimes set out separately and sometimes intertwined. The second section attempts to demonstrate how his analysis of Islam is based on cultural essentialism, which views Islam as an inherent threat and a stumbling block to democratic development, and to explain how his theories are both inaccurate and extremely dangerous in terms of their political and policy implications. The third section comprises an analysis of his theory’s impact on policy and its consequences for the United States.